Thermal analysis of natural fiber reinforced composites. (2023) - Renjith, R.; Nair, Rajesh P.
Abstract: Natural fiber composite materials grabs attention in modern industrial world. Evaluation of mechanical and thermal properties of composite requires lot of experimentation. In this paper an attempt is made to predict mechanical and thermal properties of natural fiber composite from mathematical relations. Different natural fibers and epoxy matrix were considered for the property prediction. Mechanical and thermal properties of composites were predicted using Halpin-Tsai and Chamis model respectively. Most common natural composite in traditional boat construction is wood. Here NFRP material is used as an alternative to wood. Stress concentration occurs on marine structures due to openings provided for electrical and plumping lines. In order to simulate the structural stability with NFRP material, a rectangular plate is selected for the study. The predicted properties used to study effect of thermal variation of plate with hole. Finite element model was developed to study the stress concentration over different hole diameter. L/D ratio is selected as the parameter for the study. L/D ratio versus stress plot revealed that structure is unsafe if the ratio is above 6.